Weaving theoretical-methodological considerations for a Critical, Transforming and Meaningful Environmental Education (Research, Society and Development, 2022)
Faced with the progressive degradation of nature, we question how Environmental Education - EE can contribute to the critical reflection of the challenges imposed by the socio-environmental crisis. The socio-environmental problem, due to its complex nature, does not allow simple answers, it challenges traditional teaching methods, requires new action strategies in educational practice, new teaching-learning and knowledge production methods, new alternative pedagogies that consider multidimensionality of its causes. In this context, this article, part of a doctoral research in progress, proposes a theoretical-methodological discussion on the possibility of knowledge construction, development of competences and alternative pedagogical practices for EE in the light of the Theory of Complexity, of the Dialogue of Knowledge and Critical Meaningful Learning - ASC. Conducted through a methodological procedure of bibliographic review, with a qualitative approach, the research was developed around the teachings of Edgar Morin (1977, 2000, 2002, 2005, 2011), Enrique Leff (2001, 2011, 2012, 2018), David Ausubel ( 2003), Marcos Moreira (1999, 2000, 2011) and Paulo Freire (2000). These authors propose epistemological theories and methodological procedures that are important today. It was concluded that these theoretical references are relevant and can contribute to the advancement of discussions on the planetary crisis and on the epistemological reflections of teaching-learning in EE, providing new educational paths more focused on the student, aiming at the construction of contextualized environmental knowledge. , significant, transformative, the formation of critical, reflective, participatory subjects, with the skills to face the challenges of the socio-environmental crisis.